Social identity and social integration: a meta-analysis exploring the relationship between social identity and social integration - Hu, Jieyi; Cheung, Chau Kiu Jacky (Frontiers in Psychology, 2024)
Social identity formation is crucial for psychosocial development, particularly in the case of migrating adults. A body of research exploring how social identity influences social integration among migrants shows that social identity affects social integration through a range of moderators and procedures. This study reports on a meta-analysis of 33 studies with 47 cases (total N = 33777; Fisher’s z = .33, moderate effects) examining the relationship between social identity and social integration in research conducted from 2005-2020. The research findings suggest that social identity can affect social integration directly without any moderators, indicating that most of the identified moderators in the previous studies are sample-specific variables. More importantly, the effects of various aspects of identities exert similar degrees of impact (moderate effect) on social integration; in other words, the usefulness of analyzing different aspects of social identity on social integration is challenged.